The Uncertainty Surrounding the Burden of Post-acute Consequences of Dengue Infection. Issue 9 (September 2019) - Hung, Trinh Manh; Wills, Bridget; Clapham, Hannah E.; Yacoub, Sophie; Turner, Hugo C.
Abstract : Post-acute consequences currently form a significant component of the dengue disability-adjusted life year (DALY) burden estimates. However, there is considerable uncertainty regarding the incidence, duration, and severity of these symptoms. Further research is needed to more accurately estimate the health and economic burden of these dengue manifestations.